Antibiotic Prophylaxis for Percutaneous Endoscopic Gastrostomy in Children: A Randomised Controlled Trial. Issue 3 (4th March 2021) - Alessandri, Francesco; Strisciuglio, Caterina; Borrazzo, Cristian; Cozzi, Denis; Romano, Claudio; Betalli, Pietro; Villa, Maria Pia; Parisi, Pasquale; Ziparo, Chiara; Rocco, Monica; Evangelisti, Melania; Pugliese, Francesco; et al.
ABSTRACT: Objectives: Paediatric studies on the role of antibiotic prophylaxis in the prevention of postoperative infections in children undergoing percutaneous endoscopic gastrostomy (PEG) are lacking. The aim of this study was to assess if a single dose of co-amoxiclav before PEG can decrease the rate of peristomal wound and systemic infection in children. Methods: In this prospective, randomised, double-blind, multicentre trial, children undergoing PEG were randomized to antibiotic prophylaxis with co-amoxiclav versus placebo and the rate of local and systemic infections were assessed. Results: Of the 106 patients considered for inclusion, 49 patients were randomized. In the per-protocol analysis, the occurrence of wound infection was 5% (1/20) in the antibiotic group and 21% (4/19) in the placebo group ( P  = 0.13, 16% difference in proportions, odds ratio [OR] 0.19, 95% confidence interval [CI] 0.02–1.9). The occurrence of systemic infection was 9% (2/22) in the antibiotic group and 27.2% (6/25) in the placebo group [ P  = 0.17, 18% difference in proportions, OR 0.32, 95% CI 0.06%–1.80%]. Similar results were obtained in intention-to-treat analysis. Interestingly, the overall infection rate was significantly higher in the placebo group as compared with the antibiotic group (40% vs 13.6%; P  = 0.04) and the duration of hospital stay was significantly longer in the placebo group as compared with the antibiotic group (4.4 ± 1.6 vs 3.5 ± 1.05; P  = 0.02). The number-needed-to-treat (NTT) to prevent 1 peristomal infection on average are 6.7 patients. Conclusions: A preoperative dose of co-amoxiclav reduces the overall infection rate and the duration of hospital stay. Our data suggest that antibiotic prophylaxis should be recommended in every children undergoing PEG placement.